Transformacje wergiliańskie. Wergiliusz w XXI wieku (Vergilian Transformations: Vergil in the Twenty-First Century) - Piętka, Radosław (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2025)
The paper offers a concise survey of Vergil’s presence in contemporary culture, taking into consideration various contexts such as literature, film, comics, and music. Additionally, it explores the connection between Vergil’s works and the current debate on the literary canon.